2007
DOI: 10.1101/sqb.2007.72.063
|View full text |Cite
|
Sign up to set email alerts
|

The Lateral and Dorsal Neurons ofDrosophila melanogaster:New Insights about Their Morphology and Function

Abstract: This chapter summarizes our present knowledge about the master clock of the fruit fly at the neuronal level. The clock is organized in distinct groups of interconnected pacemaker neurons with different functions. All of these neurons appear to communicate with one another in order to produce the species-specific activity rhythm, which is organized in morning (M) and evening (E) activity bouts. These two activity components are differentially influenced by distinct groups of pacemaker neurons reminiscent of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 53 publications
3
79
1
Order By: Relevance
“…4 E and F). This result explains the previous observations that LNv neurons establish presynaptic contacts within the aMe (44) and suggests that these contacts are on the postsynaptic sites of the LNv neurons themselves. Thus, similar to DCN neurons (see above), the two clusters of LNv neurons appear to relay information across the two optic lobes.…”
Section: Denmark Reveals Progressive Developmental Specialization Ofsupporting
confidence: 81%
See 1 more Smart Citation
“…4 E and F). This result explains the previous observations that LNv neurons establish presynaptic contacts within the aMe (44) and suggests that these contacts are on the postsynaptic sites of the LNv neurons themselves. Thus, similar to DCN neurons (see above), the two clusters of LNv neurons appear to relay information across the two optic lobes.…”
Section: Denmark Reveals Progressive Developmental Specialization Ofsupporting
confidence: 81%
“…4 A and A′). Previous publications revealed that projections of PDF-expressing LNv neurons elongate ventrally in the ipsilateral accessory medulla (aMe) and arborize on the surface of both ipsilateral and contralateral medulla (42,44). In addition, the same authors found that the presynaptic marker, nSyb::GFP, was mostly expressed in the projections at the medulla surface, indicating that they correspond to LNvs' axonal terminations.…”
Section: Denmark Reveals Progressive Developmental Specialization Ofmentioning
confidence: 53%
“…In contrast, the s-LN v seem to be not involved in sleep-arousal regulation but are rather important for maintaining circadian rhythmicity under DD (reviewed by Helfrich-Förster et al, 2007b). One caveat in clearly distinguishing the function of s-LN v and l-LN v is the fact that both cell clusters express the neuropeptide PDF and, as a consequence, Pdf-GAL4 drives expression in both subsets of clock neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In the D. melanogaster brain, six groups of neurons that express a set of circadian clock genes have been identified, and each neuron group appears to have a different role in behavioural rhythms (Helfrich-Förster et al, 2007;Grima et al, 2004;Stoleru et al, 2004;Rieger et al, 2006). Although in D. melanogaster circadian clock genes and neurons are well known, photoperiodic responses in this species are very shallow and difficult to assay.…”
Section: Introductionmentioning
confidence: 99%